2016
DOI: 10.1093/ejo/cjw060
|View full text |Cite
|
Sign up to set email alerts
|

Changes in white spot lesions following post-orthodontic weekly application of 1.25 per cent fluoride gel over 6 months—a randomized placebo-controlled clinical trial. Part I: photographic data evaluation

Abstract: The protocol wasn't published before trial commencement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 76 publications
0
14
0
2
Order By: Relevance
“…[4][5][6]15 Although this may bring a slight optical abatement of WSL within the first 12 months following debracketing, it rarely provides for an esthetically acceptable improvement in dentofacial appearance. 8,9,16 Resin infiltration of postorthodontic WSL has been shown to be more effective in achieving a clinically relevant camouflage effect with adjacent enamel, based on short-and mid-term studies, case reports and in vitro research. 8,[10][11][12]17,18 However, a common question raised by both patients and clinicians concerns the long-term durability of the results achieved.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[4][5][6]15 Although this may bring a slight optical abatement of WSL within the first 12 months following debracketing, it rarely provides for an esthetically acceptable improvement in dentofacial appearance. 8,9,16 Resin infiltration of postorthodontic WSL has been shown to be more effective in achieving a clinically relevant camouflage effect with adjacent enamel, based on short-and mid-term studies, case reports and in vitro research. 8,[10][11][12]17,18 However, a common question raised by both patients and clinicians concerns the long-term durability of the results achieved.…”
Section: Discussionmentioning
confidence: 99%
“…Remineralization by local fluoride application may arrest lesion progression 3 and, in combination with tooth brushing abrasion, bring about some improvement in the appearance of WSL within the first few months following debonding, [4][5][6] however, rarely to an extent that provides for an esthetically acceptable dentofacial appearance. [7][8][9] In contrast, the technique of resin infiltration (Icon, DMG) of postorthodontic enamel decalcifications yields esthetically more satisfying results. A recent split-mouth randomized controlled trial (RCT) revealed that there was a significant and clinically relevant abatement of color-and lightness differences between infiltrated WSL and sound adjacent enamel, whereas there were no significant changes in untreated control-WSL in the same time.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, Ogaard et al [ 27 ] concluded that high-concentration fluoride solutions are far more effective than low-concentration ones. Bock et al [ 28 ] studied WSL changes in response to weekly 1.25% fluoride gel application after fixed orthodontic treatment. Their results did not show any significant positive effects for high-dose fluoride on post-orthodontic WSL development.…”
Section: Discussionmentioning
confidence: 99%
“…Although oral hygiene instructions were provided, controlling for individual behavior has been shown to be very difficult. 24 Another limitation was that only right-handed patients were accepted for the study because handedness may influence brushing efficiency. In addition, the absence of analyses of patients' plaque and gingivitis scores was another limitation of the study.…”
Section: Discussionmentioning
confidence: 99%